2018
DOI: 10.3390/en11112943
|View full text |Cite
|
Sign up to set email alerts
|

MHD Mixed Convection in a Lid-Driven Cavity with a Bottom Trapezoidal Body: Two-Phase Nanofluid Model

Abstract: The current work examines the effects of a bottom trapezoidal solid body and a magnetic field on mixed convection in a lid-driven square cavity. The Al 2 O 3 -water nanofluid used is assumed to obey Buongiorno’s two-phase model. An isothermal heater is placed on the bottom base of the trapezoid solid body, while the cavity’s vertical walls are kept cold at temperature T c . The top moving wall and the remaining portions of the cavity’s bottom wall are thermally insulated. The Galerkin weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In [ 70 ], the influence of an Al 2 O 3 –water nanofluid on laminar natural convection heat transfer was investigated while a magnetic field was present in an open cavity. The heat-transfer mechanism under study was natural convection.…”
Section: The Role Of Cavities In Nanofluid Transportmentioning
confidence: 99%
“…In [ 70 ], the influence of an Al 2 O 3 –water nanofluid on laminar natural convection heat transfer was investigated while a magnetic field was present in an open cavity. The heat-transfer mechanism under study was natural convection.…”
Section: The Role Of Cavities In Nanofluid Transportmentioning
confidence: 99%
“…The obtained results explained that, the Nusselt number increases by decreasing and the inclination. The effect of an external magnetic field on nanofluid mixed convective heat transfer in a lid‐driven square cavity with a bottom trapezoidal body was investigated numerically by Sadiq et al [25]. The effects of the bottom base length of the trapezoidal body, nanoparticles volume fraction, Hartmann and Richardson numbers were examined.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the larger the nanoparticle size, the greater the number of local Nusselt. Adil et al [18] investigated the effect of nanoparticle augmentation on the heat transfer rate of nanofluids Cu-water between the hot bottom trapezoidal solid and the square cavity for different Richardson and Hartmann numbers, where he found concluded that natural convection is dominant in the case of a large Richardson number In this paper, a numerical study carried out for the natural convection of stationary laminar heat transfers in a closed rectangular cavity with a local source of internal volumetric heat generation. An Ethylene glycol-copper nanofluid crosses this ring.…”
Section: Introductionmentioning
confidence: 99%